VISIR: experiences and challenges - Tawfik, Mohamed (2014)
It is of crucial importance the integration of practical sessions in engineering curricula owing to their significant role in understanding engineering concepts and scientific phenomena. However, the lack of practical sessions due to the high costs of the equipment and the unavailability of instructors has caused a significant declination in experimentation in engineering education. Remote laboratories have tackled this issues providing online reusable and shared workbenches unconstrained by neither geographical nor time considerations. Thereby, they have extremely proliferated among universities and integrated into engineering curricula over the last decade. This contribution compiles diverse experiences based on the deployment of the remote laboratory, Virtual Instrument Systems in Reality (VISIR), on the practices of undergraduate engineering grades at various universities within the VISIR community. It aims to show the impact of its usage on engineering education concerning the assessments of students and teachers as well. In addition, the paper address the next challenges and future works carried out at several universities within the VISIR community.